SORPTION KINETICS AND ISOTHERMES OF Cu2+ IONS FOR NEW IONITE BASED ON VERMICULITE (Scientific journal of the Fergana State University, 2023)
This paper presents the results of the study of the sorption of Cu2+ ions in artificial solutions to the ion obtained on the basis of vermiculite at 293, 303 and 313 K, the duration of sorption to equilibrium (18 hours) and at different concentrations. The kinetics of the processes were studied, and Langmuir and Freundlix isothermal models were used to represent the adsorption mechanism at equilibrium. The isotherm parameters calculated on the basis of the obtained results are R2(0,998-0,9998). value was found to be consistent in all isothermal models. According to the Langmuir isotherm model, qmax = 40,161 mg / g, and according to the Freundlix isotherm model, n = 0,277. This indicates a high sorption of Cu2+ ions into the ionite based on vermiculite.